2004
DOI: 10.1158/0008-5472.can-04-0437
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Containing Nucleosides as Potential Delivery Agents for Neutron Capture Therapy of Brain Tumors

Abstract: The purpose of the present study was to evaluate both in vitro and in vivo a series of boron-containing nucleosides that potentially could be used as delivery agents for neutron capture therapy. The rationale for their synthesis was based on the fact that proliferating neoplastic cells have increased requirements for nucleic acid precursors, and, therefore, they should preferentially localize in the tumor. A series of 3-carboranlyalkyl thymidine analogs has been synthesized and a subset, designated N4, N5, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 71 publications
1
92
0
Order By: Relevance
“…Data from earlier studies suggested that phosphorylation by TK1 was required for uptake and retention of the N5-2OH in malignant cells both in vitro and in vivo (Al-Madhoun et al, 2004; Barth et al, 2004Barth et al, , 2008. However, little information is available regarding the complete intracellular metabolism of N5-2OH, including its potential incorporation into DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from earlier studies suggested that phosphorylation by TK1 was required for uptake and retention of the N5-2OH in malignant cells both in vitro and in vivo (Al-Madhoun et al, 2004; Barth et al, 2004Barth et al, , 2008. However, little information is available regarding the complete intracellular metabolism of N5-2OH, including its potential incorporation into DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The first generation 3CTA 3-[5-{2-(2,3-dihydroxyprop-1-yl)-o-carboran-1-yl}pentan-1-yl]thymidine (N5-2OH; Fig. 1) is an excellent substrate of TK1 and exhibits high uptake and retention in TK1-expressing tumor cells in vivo Barth et al, 2004Barth et al, , 2008. The favorable in vivo profile of N5-2OH led to successful preclinical NCT of rats bearing intracerebral RG2 glioma (Barth et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…An important advantage of direct i.c. delivery of the capture agent, whether it be a high molecular weight bioconjugate or a low molecular weight agent, such as the boronated nucleoside, N5-2OH (46), is that the tumor boron concentration can be increased without a concomitant increase in the blood concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several boron-containing analogues of the biochemical precursors of nucleic acids, including purines, pyrimidines, nucleosides, and nucleotides, have been synthesized and evaluated in cellular and animal studies (55 -58). Some of these compounds, such as h-5-o-carboranyl-2V -deoxyuridine (compound 4) and the 3-(dihydroxypropyl-carboranyl-pentyl)thymidine derivative N5-2OH (compound 5), have shown low toxicities, selective tumor cell uptake, and significant rates of phosphorylation into the corresponding nucleotides (59,60). Intracellular nucleotide formation potentially can lead to enhanced tumor uptake and retention of these types of compounds (59).…”
Section: Low Molecular Weight Agentsmentioning
confidence: 99%
“…injection or convection enhanced delivery of the borononucleoside N5-2OH (compound 5) were both effective in selectively delivering potentially therapeutic amounts of boron to rats bearing i.c. implants of the F98 glioma (60). Direct i.t.…”
Section: Optimizing Delivery Of Boron-containing Agentsmentioning
confidence: 99%